Competing imaginations for teaching and learning: The findings of research into a Christian approach to teaching and learning called What If Learning - Cooling, Trevor (International journal of Christianity & education, 2015)
What If Learning is an approach to help teachers re-frame teaching and learning to support the Christian ethos of a school. This article presents the findings of research carried out with 14 teachers, in three state-funded church secondary schools in England. The findings provide an important insight into teachers’ pedagogic practice. The article concludes that teachers’ assumptions about knowledge, pedagogy and theology are filtered through their prior assumptions about what it means to teach ‘Christianly’ and also by assumptions about pedagogy embedded within English education policy. What If Learning required them to re-frame their practice in the light of a Christian worldview, and even though they were teaching in church schools this was the first time some of the participants had experienced this.